What is a ‘Wilton scraper’? Perspectives from the Late Holocene assemblage of Balerno Main Shelter, Limpopo Province, South Africa. - Guillemard, Iris; Porraz, Guillaume (Southern African Humanities, 2019)
Wilton microlithic scrapers are widespread stone tools of the southern African Holocene Later Stone Age. Studied and classified in various ways, there are still many questions regarding their fabrication, function and hafting. Ultimately, it comes down to one question: are all these scrapers the same tool? By focusing on the late Holocene (end-)scraper assemblage from Balerno Main Shelter in the Limpopo Province of South Africa, the scraper variability in one site is investigated through a morpho-functional analysis. The results of our analysis led us to individualise three types of tools that vary primarily with regard to the characteristics of their passive units (the assumed prehensile part). This classification is accompanied by hypotheses about the hafting and functioning of these scrapers and carries implications for the categorisation of Wilton scrapers throughout southern Africa.